Hydraulic fracturing chemicals and fluids technology - Fink, Johannes Karl (Gulf Professional Publishing, 2020)
Petroleum engineers continue to need cost saving and environmentally sustainable products and methods for today's hydraulic fracturing operations. Hydraulic Fracturing Chemicals and Fluid Technology, Second Edition, continues to deliver an easy-to-use manual of fluid formulations to meet specific job needs. Enhanced with more environmental aspects, this reference helps engineers and fluid specialists select and use the appropriate chemicals for any hydraulic fracturing job. New information concerning nanotechnology applications such as wellbore sealant and proppants are added to enhance operations in a sustainable manner while saving on production costs. Other updates include low recovery of fracturing water in shale, surfactants for waterless hydraulic fracturing, and expanded produced water treatment. Rounding out with updated references and patents for easy reference, Hydraulic Fracturing Chemicals and Fluid Technology, Second Edition, gives engineers a critical guide on selecting better products to boost productions while strengthening environmental enhancement and consideration.